2021
DOI: 10.1371/journal.ppat.1009557
|View full text |Cite|
|
Sign up to set email alerts
|

Pseudomonas aeruginosa–induced nociceptor activation increases susceptibility to infection

Abstract: We report a rapid reduction in blink reflexes during in vivo ocular Pseudomonas aeruginosa infection, which is commonly attributed and indicative of functional neuronal damage. Sensory neurons derived in vitro from trigeminal ganglia (TG) were able to directly respond to P. aeruginosa but reacted significantly less to strains of P. aeruginosa that lacked virulence factors such as pili, flagella, or a type III secretion system. These observations led us to explore the impact of neurons on the host’s susceptibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…42 It was also more recently shown that during P. aeruginosa infection of the cornea, inflammation is promoted by TRPV1, associated with CGRP-mediated recruitment of neutrophils with reduced bactericidal activity. 53 Clearly, the role(s) of TRPA1 and TRPV1 nociceptors in modulating progression of infection and associated disease pathology via immune cell recruitment/function is complex and further studies will help elucidate tissue and/or pathogen specificity of their involvement.…”
Section: Introductionmentioning
confidence: 99%
“…42 It was also more recently shown that during P. aeruginosa infection of the cornea, inflammation is promoted by TRPV1, associated with CGRP-mediated recruitment of neutrophils with reduced bactericidal activity. 53 Clearly, the role(s) of TRPA1 and TRPV1 nociceptors in modulating progression of infection and associated disease pathology via immune cell recruitment/function is complex and further studies will help elucidate tissue and/or pathogen specificity of their involvement.…”
Section: Introductionmentioning
confidence: 99%
“…Corneal nerve density was determined as described before with minor modifications. 34 , 35 Briefly, Z-stack images were acquired from the central and pericentral regions of the cornea (∼500 µm 2 /area) with a comparable thickness (∼50 µm) using the TCS SP8 laser confocal microscope. The images were collapsed to two dimensions and converted to a binary image using ImageJ 1.52p (National Institutes of Health, Bethesda, MD, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Calcitonin gene-related peptide (CGRP) is another factor that influences corneal homeostasis by increasing wound healing and promoting tissue healing phenotypes in macrophages (M2) 154 , 155 . Conversely, CGRP is also known to play a role in photophobia and may limit the ability of the cornea to resist infection 156 , 157 . Vasoactive intestinal peptide (VIP) is another neuropeptide produced at the ocular surface, and this factor has been shown to aid in limiting disease in diabetic keratopathy, bacterial keratitis, and allergic conjunctivitis 158 – 161 .…”
Section: Neuroimmune Axis and The Modulation Of Mucosal Immunitymentioning
confidence: 99%